If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-10t + -3) + 6t = 75 Reorder the terms: 3(-3 + -10t) + 6t = 75 (-3 * 3 + -10t * 3) + 6t = 75 (-9 + -30t) + 6t = 75 Combine like terms: -30t + 6t = -24t -9 + -24t = 75 Solving -9 + -24t = 75 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -24t = 75 + 9 Combine like terms: -9 + 9 = 0 0 + -24t = 75 + 9 -24t = 75 + 9 Combine like terms: 75 + 9 = 84 -24t = 84 Divide each side by '-24'. t = -3.5 Simplifying t = -3.5
| 5t+s=t-2 | | 4x+3(x-2)=-5(x-4)-6 | | 6u+48=4(u+7) | | 7x=-91 | | 3(5-3p)=87 | | -8-n=-3(2x-4) | | .06x+0.07(18500-x)=1155 | | 4.8+9.2= | | -x-3y=9 | | 9x^2-12x+8=0 | | 5.6p=22.4 | | 63=-3(1-2x) | | x-3-2x=0 | | 3u+7=-5 | | 0.5(-4+6x)=33.3x+66.6(x+9) | | 15x-5=1+12x | | 25x*76= | | 2-3a=7-2(2a+3) | | 7x+6(-x-17)=-109 | | -8(m-8)=120 | | 7x+.43=y | | -9x+4=-6x+17 | | 12x-8=6x+22 | | 7x-6x-102=109 | | 2x+116-116=180-116 | | 7x-(3x+4)=-2(2x-1)+10 | | 2x^4+x^3-9x^2-4x+4=0 | | 97=4(2+3k)+5 | | 5y-3=8+4(y-2) | | 2(9.2-8)+2(9.2-8)= | | 3d-8=7+8d | | -29=5(2x-1)+2a |